Readiness of MSMEs in Facing the Industrial Revolution 5.0 through Green Economy - Manan, Mohammad Athian; Nursari, Ayu; Sejati, Hiro; Yoesseri, Dafa; Mareta, Youlanda Tri (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to determine the readiness of MSMEs in Bandar Lampung City in facing the Industrial Revolution 5.0 through the implementation of the Green Economy. Methodology: This research uses descriptive quantitative analysis, qualitative analysis and descriptive simple linear regression using SPSS software version 23. The population in this study were 118,533 MSMEs in Bandar Lampung City. The research sample was obtained using the Slovin formula as many as 100 MSMEs. Results: The results show that MSMEs in Bandar Lampung City demonstrate a good understanding of the Green Economy, with an average score of 4.09.  However, despite this high understanding, the implementation of Green Economy principles in specific aspects such as waste management and social media campaigns still needs to be improved. In addition, MSMEs in Bandar Lampung City show high readiness in facing the Industrial Revolution 5.0, with an average score of 4.51. MSMEs have started to integrate digital technology and automation in their operations. Limitations: The limitations of this study include geographical coverage limited to MSMEs in Bandar Lampung City, so the results may not be generalizable to other regions.  Additionally, this study does not focus on MSMEs with specific types of businesses, so the results may not capture the specific characteristics or challenges that may be faced by particular business sectors. Contribution: The results of this study are expected to serve as a reference for policy makers in formulating more effective strategies to support MSMEs in adopting environmentally friendly technologies.